2012
DOI: 10.1111/j.1365-2656.2012.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

APalaearctic migratory raptor species tracks shifting prey availability within its wintering range in theSahel

Abstract: Summary1. Mid-winter movements of up to several hundreds of kilometres are typical for many migratory bird species wintering in Africa. Unpredictable temporary food concentrations are thought to result in random movements of such birds, whereas resightings and recoveries of marked birds suggest some degree of site fidelity. Only detailed (e.g. satellite) tracking of individual migrants can reveal the relative importance and the causes of site choice flexibility and fidelity. The present study investigates how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 43 publications
9
141
1
2
Order By: Relevance
“…Trierweiler et al (2013) reported that individual Montagu's Harriers (Circus pygargus) followed patterns of vegetation presence that presumably reflect food availability, and a similar pattern has been found in Lesser Kestrels (Falco naumanni; Catry et al 2011). Less is known of itinerancy in passerines.…”
Section: Methodsmentioning
confidence: 83%
“…Trierweiler et al (2013) reported that individual Montagu's Harriers (Circus pygargus) followed patterns of vegetation presence that presumably reflect food availability, and a similar pattern has been found in Lesser Kestrels (Falco naumanni; Catry et al 2011). Less is known of itinerancy in passerines.…”
Section: Methodsmentioning
confidence: 83%
“…However, the hypothesized link between movements and seasonal regional resources throughout the annual cycle has never been properly established, and the precise timing of annual individual schedules relative to seasonally induced local dynamics in habitats, food resources, and climate remains restricted to parts of the annual cycle in long-distance migrants ( 6 8 , 13 , 15 , 16 , 25 ). In order to establish potential links between resources and annual bird movements, we have combined the results of high–temporal resolution tracking of individual birds with monitoring variation in local ecological conditions across the seasonally changing globe.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerating vegetation growth during spring green-up provides another potentially high food availability, also known as surfing the green wave ( 6 , 13 ), although, for insectivores, the food peak is generally delayed. Avoiding decreasing vegetation conditions could also drive movements ( 15 , 16 ). …”
Section: Introductionmentioning
confidence: 99%
“…A particularly exciting prospect is the increasingly detailed and complete environmental annotation of movement paths. MODIS sensors have the potential to provide global information on greenness and other land-surface attributes down to 8-day or even daily frequency, and researchers have begun to successfully use these to relate movement to resource availability (73). Remote-sensing-supported predictions of climate conditions in daily and 1-km resolution (74) hold the promise to extend such annotations to ecologically even more meaningful variables.…”
Section: Science Sciencemagorgmentioning
confidence: 99%